Estudo comparativo sobre a Educação Matemática presente em currículos: Brasil e Uruguai - Rosenbaum, Luciane Santos (2014)
This research aims to develop comparative analyses about organization and curriculum development in the area of mathematics education, between Brazil and Uruguay, considering the importance of seeking solutions to challenging problems related to curriculum design. This is a qualitative research. Using literature in the area, we are going to analyze in the prescribed and presented curricula, the evidence or not of the knowledge of research results in Mathematics Education in the official documents of these countries. From interviews with actors of the curriculum from the two countries, we identified common aspects and specific items of mathematics curricula and forms of organization. We raised data that show acceptance or rejection of teachers of mathematics to the curriculum guidelines in the official documents, looking for evidences about the effectiveness of such curricula in the classroom. The analyzes reveal many similarities concerning contents in the curricular requirements and evidence of the influence of research results in Mathematics Education in curriculum development of the countries surveyed. However, we found differences in implementation, organization of the curriculum and in the attitude of teachers concerning recommendations